Reforming Government Debt Markets in MENA - Garcia-Kilroy, Catiana; Silva, Anderson Caputo (2012)
This paper examines the current stage of development of government securities markets in the non-GCC MENA region focusing in five countries that have government bond markets with a minimum size and greater potential for market development: Egypt, Jordan, Lebanon, Morocco and Tunisia. The analysis focuses on the five key building blocks that normally sustain deep and liquid public debt markets: (i) money markets; (ii) primary market (issuance policy and placement mechanisms); (iii) secondary market organization; (iv) investor base; and (v) clearing and settlement infrastructure. The study shows that despite country differences, several common weaknesses in the key building blocks explain the underdevelopment of MENA bond markets. Most important among these are a symbiotic relationship between banks and Governments caused by lack of alternative investments that makes banks act as captive demand and dominate bond markets, opportunistic primary issuance practices, and excess liquidity in the financial system. These demand and supply characteristics have led to highly concentrated buy-and-hold portfolios by banks and State-owned institutions, poor price discovery and lack of liquidity in secondary markets. A set of actions to unlock market development in MENA is proposed involving measures in all key building blocks - from improvements in monetary policy implementation and liquidity management to enhancements in issuance practices, price transparency, and clearing & settlement infrastructure. Measures to improve the role of mutual funds and foster foreign investor presence are also of utmost importance to increase competition and investor diversification in these markets.